Avaliação da contaminação por elementos metálicos dos sedimentos do Estuário Santos - São Vicente - Hortellani, Marcos Antonio; Sarkis, Jorge E. S.; Abessa, Denis Moledo de Souza [UNESP]; Sousa, Eduinetty C. P. M. (Sociedade Brasileira de Química, 2008)
Three approaches were applied to evaluate metal contamination in 41 sediment samples from the Santos - São Vicente Estuarine System: normalization to Al, statistical analysis and sediment quality guidelines (SQGs). The results showed increases in the concentrations of Zn, Ni, Pb, Cd, Cr and Hg, which seemed to be associated with human activities. The levels of Al, Fe and Co probably were associated with crustal material or natural weathering processes. About 45% of the samples presented concentrations exceeding TEL-ERL, levels occasionally associated with adverse biological effects. Four of these samples presented concentrations above PEL-ERM, levels frequently associated with adverse biological effects.
Assessment of metallic element contamination in sediments from the Santos - São Vicente Estuarine System
Keywords: sediments; metal contamination; normalization